About one method of the automated estimation of acoustic properties of the hall the geometrical acoustics method - Усик, Виктория Валерьевна; Мягкий, Игорь Григорьевич (Eastern-European Journal of Enterprise Technologies, 2012)
The researches of space-planning decisions auditoria to provide optimal acoustic properties in terms of geometrical acoustics. Developed software that allows you to build and verify the proposed sound-reflecting surface in CAD AutoCad.